Kontribusi Brand Awareness dan Brand Image terhadap Minat Pembelian IPhone pada Mahasiswa Pendidikan Ekonomi Universitas Sebelas Maret (International Forum of Researchers and Lecturers, 2025)
This study aims to examine the influence of brand awareness (X1) and brand image (X2) on the purchase intention (Y) of iPhone among students of the Economic Education program at Universitas Sebelas Maret. The background of this study is based on the increasing preference of students towards the iPhone, which holds high exclusivity value and strong brand image, despite being positioned in a premium price segment. This research employs a quantitative approach using a survey method through questionnaires distributed to 83 respondents selected randomly by simple random sampling technique. The research instruments were tested for validity and reliability, and the data were analyzed using multiple linear regression analysis. The results indicate that both X1 and X2 have a significant effect on Y. The implications of these findings suggest that marketing strategies emphasizing the development of a strong and exclusive brand image can enhance consumers’ purchase intention, particularly among students. This study is expected to serve as a reference for marketers in designing effective and targeted promotional strategies for the higher education market segment.